PKC-α is involved in the signaling of phagocytosis induced by two snake venom secretory PLA2S in macrophages - Zuliani, Juliana Pavan (2024)
Phagocytosis, an essential process for host defense, requires the coordination of a variety of signaling reactions. MT-II, an enzymatically inactive Lys49 phospholipase A2 (PLA2) homolog, and MT-III, a catalytically-active Asp49 PLA2, are known to activate phagocytosis in macrophages. In this study, the signaling pathways mediating phagocytosis, focusing on protein kinases, were investigated. Macrophages from male Swiss mice peritoneum were obtained 96 h after intraperitoneal thioglycolate injection. Phagocytosis was evaluated using non-opsonized zymosan particles in the presence or absence of specific inhibitors, as well as PKC and PKC-α localization by confocal microscopy. Moreover, protein kinase C (PKC) activity was assessed by γP32 ATP in macrophages stimulated by both PLA2s. Data showed that both sPLA2s increased phagocytosis. Cytochalasin D, staurosporine/H7, wortmannin, and herbimycin, inhibitors of actin polymerization, PKC, phosphoinositide 3-kinase (PI3K), and protein tyrosine kinase (PTK), respectively, significantly reduced phagocytosis induced by both PLA2s. PKC activity was increased in macrophages stimulated by both PLA2s. Actin polymerization and talin were evidenced by immunofluorescence and talin was recruited 5 min after both PLA2s stimulation. PKC and PKC-α localization within the cell were increased after 60 min of MT-II and MT-III stimulation. These data suggest that the effect of both PLA2s depends on actin cytoskeleton rearrangements and the activation of PKC, PI3K, and PTK signaling events required for phagocytosis.